2001
DOI: 10.1046/j.1365-2141.2001.02957.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of FGFR3 gene mutations in multiple myeloma patients with t(4;14)

Abstract: Summary. The t(4;14)(p16.3;q32) in multiple myeloma (MM) leads to an apparent deregulation of the FGFR3 and WHSC1/MMSET genes. FGFR3 mutations, known to be associated with genetic skeletal disorders, have also been identified in a few cases of MM (mainly cell lines) with t(4;14). We investigated FGFR3 mutations in a series of 53 MM cases; 11 cases with t(4;14) and FGFR3 overexpression were analysed using reverse transcription polymerase chain reaction, while the remaining cases were studied at DNA level. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 11 publications
(16 reference statements)
5
43
0
Order By: Relevance
“…Initial screenings performed at 5, 10, and 20 M scales identified a compound named NF449 as a potent antagonist of the FGF2/ FGFR3-inhibitory effect on RCS proliferation. 3 This effect was confirmed in detailed cell growth experiments, where 20 M NF449 caused significant rescue of the growth arrest phenotype without apparent cellular toxicity throughout its active concentration range (ϳ6 -30 M; Fig. 1A).…”
Section: Nf449 Inhibits Fgfr3 Signaling In Chondrocytes-supporting
confidence: 58%
See 3 more Smart Citations
“…Initial screenings performed at 5, 10, and 20 M scales identified a compound named NF449 as a potent antagonist of the FGF2/ FGFR3-inhibitory effect on RCS proliferation. 3 This effect was confirmed in detailed cell growth experiments, where 20 M NF449 caused significant rescue of the growth arrest phenotype without apparent cellular toxicity throughout its active concentration range (ϳ6 -30 M; Fig. 1A).…”
Section: Nf449 Inhibits Fgfr3 Signaling In Chondrocytes-supporting
confidence: 58%
“…Because the CCL3 (MIP-1␣) and CCL4 (MIP-1␤) chemokines were previously identified as transcriptional targets of FGFR3 signaling in multiple myeloma (17), 3 we determined the effect of NF449 on the FGF2-mediated accumulation of the CCL3 and CCL4 transcripts. Real-time reverse transcription-PCR analysis showed the partial NF449-mediated rescue of the CCL3 and CCL4 accumulation induced by FGF2 treatment in the OPM2 cells (Fig.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Where mutations of FGFR3 are frequent events, forexample, in bladder cancer (Cappellen et al, 1999;Billerey et al, 2001;van Rhijn et al, 2001;Sibley et al, 2001), nonsense mutations inserted within its coding region may result in altered splice site selection (Valentine, 1998). This is unlikely to be the case for the majority of cancers where mutations of FGFR3 are rare (Intini et al, 2001;Karoui et al, 2001;Sibley et al, 2001), although FGFR3 may be inactivated by aberrant-splicing and activation of cryptic splice donor sites (Jang et al, 2000). In this study we have identified and characterised a novel FGFR3IIIc variant, FGFR3IIIS, which is frequently expressed in tumorigenic but rarely in nontumorigenic cells.…”
mentioning
confidence: 99%